A four-coordinate cobalt(II) single-ion magnet with coercivity and a very high energy barrier - Rechkemmer, Yvonne; Breitgoff, Frauke D.; van der Meer, Margarethe; Atanasov, Mihail; Hakl, Michael; Orlita, Milan; Neugebauer, Petr; Neese, Frank; Sarkar, Biprajit; van Slageren, Joris (Nature communications, 2016)
Single-molecule magnets display magnetic bistability of molecular origin, which may one day be exploited in magnetic data storage devices. Recently it was realised that increasing the magnetic moment of polynuclear molecules does not automatically lead to a substantial increase in magnetic bistability. Attention has thus increasingly focussed on ions with large magnetic anisotropies, especially lanthanides. In spite of large effective energy barriers towards relaxation of the magnetic moment, this has so far not led to a big increase in magnetic bistability. Here we present a comprehensive study of a mononuclear, tetrahedrally coordinated cobalt(II) single-molecule magnet, which has a very high effective energy barrier and displays pronounced magnetic bistability. The combined experimental-theoretical approach enables an in-depth understanding of the origin of these favourable properties, which are shown to arise from a strong ligand field in combination with axial distortion. Our findings allow formulation of clear design principles for improved materials. Bistable single-molecule magnets potentially allow information storage at extremely high densities. Here, the authors study an air- and moisture-stable mononuclear tetrahedral cobalt(II) complex, elucidating the origin of its pronounced magnetic bistability.